Peripheral rather than central fatigue is responsible for rowing performance improvement with oxygen supplementation - Volianitis, S.; Bjarrum, M.; Carlson, C.; Rasmussen, P.; Overgaard, A.; Fabricius-Bjerre, A.; Secher, N. H.; Nielsen, H. B.; Petersen, N. C. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Hyperoxic breathing may enhance rowing performance, presumably by restoring cerebral oxygenation (SCO2), and thus attenuating central fatigue. However, considering that hyperoxia also attenuates peripheral fatigue, the contribution of central and peripheral fatigue to rowing performance is not known. This study evaluated the effect of oxygen supplementation on cerebral and active muscle oxygenation together with central and peripheral fatigue indices, i.e., reduction in maximal voluntary contraction (MVC) and transcranial magnetic stimulated (TMS) force generation. Methods: Six competitive rowers performed 2000 m all-out exercise on a rowing ergometer in normoxia and hyperoxia (30% O2) in a randomised double blind crossover design. Arm MVC was assessed with electromyography (EMG) of the m. biceps brachii and the m. brachioradialis. Voluntary activation of the elbow flexor muscles was assessed with TMS single pulses that were delivered to the motor cortex and evoked motor potential in the biceps brachii. SCO2 and muscle (vastus lateralis) oxygenation were assessed with near infrared spectroscopy (NIRS). Results: Arterial hemoglobin O2 saturation was 92.5 +/- 0.2% during exercise in normoxia, while it was maintained at 98.9 +/- 0.2% in hyperoxia. SCO2 decreased by 11% from resting baseline during exercise in normoxia, while it was maintained during hyperoxia. Muscle oxygenation decreased equally during normoxia (-35%) and hyperoxia (-32%), while rowing performance tended to increase during hyperoxia (-3 +/- 4 s, NS). Maximal rowing in normoxia resulted in a significant reduction (7.4 +/-5.1 %) in MVC, while there was no difference in the extra force produced by TMS. Following hyperoxic exercise the MVC and TMS were not different than at rest. Discussion: These data indicate that following maximal rowing the force generating capacity of the elbow flexor muscles is attenuated but it is restored with hyperoxia and suggest that the associated performance improvement with oxygen supplementation is attributed to alleviation of peripheral fatigue.